Explanation:
f(g(x))
means we have to calculate g(x) first, and then we use that result as input value for f and calculate that as the final result.
in general, the expression for that combined function is created by putting the expression of g(x) into every place of x in f(x) :
(f○g)(x) = f(g(x)) = 2(3x + 4) + 1 = 6x + 8 + 1 = 6x + 9
therefore,
f(g(8)) = 6×8 + 9 = 48 + 9 = 57
let's try it with basic steps :
g(8) = 3×8 + 4 = 24 + 4 = 28
and then
f(28) = 2×28 + 1 = 56 + 1 = 57
so, no, the showing number "21" is not correct.
I cannot see what you did to get 21.
the only way seems to be that you calculated f(8) = 17. and then you used this 17 to replace the whole 3x and not just x and got 17 + 4 = 21.
if that is what you did, you made 2 mistakes at once.
first you used 8 as input value for f(x) and not for g(x).
so, you tried to calculate g(f(8)).
and then, as mentioned, you replaced 3x (why ? what made you think that that's a valid thing) in g(x) by that result, instead of x.